Crisis and selective adaptation in a Chinese prefecture between 2008 and 2010: a survey among industrial enterprises - Mária Csanádi; Liu Xiaoxuan (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
This paper demonstrates that despite substantial transformation towards a market economy, occasions for increased state intervention will mobilize the characteristics of redistribution in party-state systems. Such state intervention occurred through the introduction of the stimulus package in 2008 to compensate the impact of the global crisis. The present paper reflects on the impact of the crisis, the allocation of resources to enterprises in the manufacturing sector in one Chinese city based on the analysis of 445 enterprise questionnaires selected through random sampling. Results show that interventions activated the usual allocation priorities and political motivations of economic behavior of distributors and economic actors in party-states: selective distribution of resources for large and state-owned enterprises with strong ties to government institutions and banks, motivating drive for growth and connections rather than market behavior.
Keywords: F5; D78; R58; J08; O15; E24; 330; party-state model; short term shocks; adaptation; system transformation; global crisis; overheating; spatial disparities; Systemtransformation; Wirtschaftskrise; International; Wirkungsanalyse; Schock; Räumliche Verteilung; Industrie; China